# I wish to prove cos^2x-sin^2x=2cos^2x-1.

Tyler Larue | Certified Educator

calendarEducator since 2017

starTop subjects are Literature, Math, and Business

Another way of solving the problem (cos x)² - (sin x)² = 2(cos x)² - 1

is as follows:

Consider the right-hand side (RHS) of the equation: 2(cos x)² - 1

From the Pythagorean Identity, we know that (cos x)² + (sin x)² = 1

Thus substitute 1 with (cos x)² + (sin x)² in the RHS of the equation:

2 (cos x)² - ((sin x)² + (cos x)² ).

Expand to give 2(cos x)² - (sin x)² - (cos x)² = (cos x)² - (sin x)² (as given by the LHS of the original equation).

Thus (cos x)² - (sin x)² = 2 (cos x)² - 1

check Approved by eNotes Editorial

Inna Shpiro | Certified Educator

calendarEducator since 2013

starTop subjects are Math, Science, and Literature

Alternatively, we can start with the right-hand side and show that it equals the left hand side.

Rewrite the right hand side, 2(cosx)² - 1, as (cosx)² + (cosx)² - 1, which can also be rewritten as

(cosx)² - (1 - (cosx)²) by switching the order of the second and third terms and factoring out negative sign.

Then, according to Pythagorean Identity, (sinx)² + (cosx)² = 1, the expression in the parenthesis, 1 - (cosx)², can be replaced by (sinx)²:

(cosx)² - (1 - (cosx)²) = (cosx)² - (sinx)².

This, we have shown that (cosx - (sinx = 2(cosx)² - 1.

check Approved by eNotes Editorial

Tushar Chandra | Certified Educator

calendarEducator since 2010

starTop subjects are Math, Science, and Business

We have to prove that: (cos x)^2 - (sin x)^2 = 2*(cos x)^2 - 1

Starting with the left hand side:

We use the relation (cos x)^2 + (sin x)^2 = 1 or (sin x)^2 = 1 - (cos x)^2

=> (cos x)^2 - (sin x)^2

=> (cos x)^2 - (1 - (cos x)^2)

=> (cos x)^2 - 1 + (cos x)^2)

=> 2(cos x)^2 - 1

which is the right hand side.

Therefore we prove that (cos x)^2 - (sin x)^2 = 2*(cos x)^2 - 1

check Approved by eNotes Editorial

giorgiana1976 | Student

You can manipulate only the left side of the equation.

For this reason, you'll use the Pythagorean identity:

(sin x)^2 + (cos x)^2 = 1

(sin x)^2 = 1 - (cos x)^2

You'll substitute (sin x)^2 to the left side of the equation:

(cos x)^2 - [1 - (cos x)^2] = 2 (cos x)^2 - 1

We'll remove the brackets to the left side:

(cos x)^2 - 1 + (cos x)^2 = 2 (cos x)^2 - 1

We'll combine like terms and we notice that LHS = RHS:

2 (cos x)^2 - 1 = 2 (cos x)^2 - 1